PENGARUH VARIASI KECEPATAN DAN BEBAN TERHADAP JARAK TEMPUH PADA GEROBAK SORONG BERMESIN MOTOR MIO SPORTY 110 CC - Lestariningsih, Wiji (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to determine the impact of speed and load variations on the travel distance of a motorized wheelbarrow with a 110 cc Mio Sporty engine. Choosing the right transport equipment, such as a motorized wheelbarrow, can enhance work efficiency by facilitating and speeding up the transportation of construction materials, with its capacity depending on the volume and durability of the wheelbarrow materials. Using an experimental method with speed variations of 15 km/h, 20 km/h, and 25 km/h, and loads of 40 kg, 60 kg, and 80 kg, along with 30 ml of Pertalite fuel, road tests were conducted to find speed and load efficiency. The results indicate that speed and load variations affect the travel distance. A speed of 20 km/h is the most efficient for the travel distance of the motorized wheelbarrow with a 110 cc Mio Sporty engine, as it shows the largest distance difference. Additionally, a load of 80 kg is the most efficient as it has the largest travel distance difference.